STRATEGIC DIVERSIFICATION ANALYSIS: BUSINESS STRATEGY DEVELOPMENT FOR MBG PROGRAM KITCHEN MANUFACTURING - Krisan Ayu; Harimukti Wandebori (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This research examines how CV XYZ can formulate appropriate business strategy to achieve growth objectives while preserving competitive advantages in the highly competitive, price-sensitive MBG market. The research employs qualitative case study methodology combining primary data through questionnaire surveys measuring competitive forces, semi-structured interviews with internal stakeholders, and document analysis, supplemented by secondary data from government documents and industry reports. Analysis applies strategic frameworks including General Environment Analysis, Industrial Analysis, competitor analysis, Resource-Based View, and Value Chain Analysis. SWOT synthesis integrates findings identifying critical strategic issues, while TOWS Matrix generates strategic alternatives evaluated through weighted criteria matrix. Analysis reveals CV XYZ possesses distinctive resources including medical-grade manufacturing expertise, comprehensive certifications (ISO 13485, CPAKB, Halal, SLHS, HACCP), proprietary software, zero-incident track record, and modular construction capability. External environment demonstrates substantial opportunity through large-scale government program requiring approximately 30,000 kitchens nationally, though tempered by intense price competition. The food safety crisis creates temporary quality premium expanding addressable market from 10-15% to 20-25% of quality-aware buyers. Three strategic alternatives emerge: Premium Niche Defense, Mass Market Penetration, and Integrated Market Leadership. Evaluation reveals Integrated Market Leadership scores 4.05, significantly ahead of alternatives (3.20 and 3.00), reflecting superior performance on growth achievement and financial returns while maintaining competitive advantage. The recommended Differentiation Strategy implements three product tiers: Premium, Standard, and Essential, Implementation follows phased quarterly approach through 2026.